Indigenous Entrepreneurship and Organizational Tensions: When Marginality and Entrepreneurship Meet - Fortin-Lefebvre, Emilie; Baba, Sofiane (Management international / International Management / Gestiòn Internacional, 2021)
This article explores how marginality influences indigenous entrepreneurship through tensions that emerge from the constant threat of seeing indigenous cultures fade away. Based on a qualitative study in Quebec, this article theorizes a process that explains how the context of marginality influences indigenous entrepreneurship. Four concurrent dynamics provide insight into the realities of indigenous entrepreneurship. This article paves the way for new lines of research on indigenous entrepreneurship, the micro-foundations of tensions, and the link between emotions and cognition in managing these tensions.